2016
DOI: 10.3340/jkns.2016.59.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Neck Clipping as the Primary Treatment Option for Both Ruptured and Unruptured Middle Cerebral Artery Aneurysms

Abstract: ObjectiveAlthough middle cerebral artery (MCA) aneurysms are less amenable to coil embolization, an increasing number of studies support favorable endovascular treatment for them. The purpose of this study is to compare the outcomes of two different treatments (surgery versus coiling) and evaluate the benefits of surgical clipping for MCA aneurysms.MethodsHere we retrospectively analyzed the outcomes of 178 ruptured and unruptured MCA aneurysms treated in patients between September 2008 and April 2012. Paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…7 In direct comparison with surgical clipping, the mortality rate after the endovascular technique was at least equal to recent published data (1.9%-2.0%). 8,9 We found a good clinical outcome (mRS Ϲ 2) in 91.3% directly after discharge and in 89.8% after long-term follow-up. In their comparative analysis, McDonald et al 7 found a similar in-hospital mortality risk, but in long-term follow-up, the outcome in surgical treatment was significantly worse than after endovascular technique.…”
Section: Comparison Between Surgical Clipping and Endovascular Techniquementioning
confidence: 68%
“…7 In direct comparison with surgical clipping, the mortality rate after the endovascular technique was at least equal to recent published data (1.9%-2.0%). 8,9 We found a good clinical outcome (mRS Ϲ 2) in 91.3% directly after discharge and in 89.8% after long-term follow-up. In their comparative analysis, McDonald et al 7 found a similar in-hospital mortality risk, but in long-term follow-up, the outcome in surgical treatment was significantly worse than after endovascular technique.…”
Section: Comparison Between Surgical Clipping and Endovascular Techniquementioning
confidence: 68%
“…Despite clipping once being the management centerpiece, the swift refinement of endovascular procedures and innovation of flow diversion devices have steadily replaced surgery as the first line of therapy for UIAs. However, certain countries still favor clipping due to its longevity, effectiveness, and the lower risk of recanalization than endovascular techniques, as well as lower procedure-related costs [75][76][77]. Consequently, whereas older patients who are unsuitable for surgery may benefit the most from endovascular procedures, clipping is considered preferable for younger patients with lower-grade aneurysms and that may be able to tolerate this intervention [76,78].…”
Section: Clipping Of Solitary Unruptured Aneurysmsmentioning
confidence: 99%
“…Likewise, MCA aneurysms, which are generally considered more easily approached by surgery, were grossly underrepresented in this study. Several authors obtained much higher rates of complete obliteration via clipping than through endovascular procedures for aneurysms in this location [77,81,82]. This is more likely a consequence of the particular configurations of MCA aneurysms, rendering it more difficult to completely occlude the neck via endovascular procedures (wide-necked, possessing a small dome-to-neck ratio, the neck encompassing one of the arterial branches, etc.)…”
Section: Clipping Of Solitary Unruptured Aneurysmsmentioning
confidence: 99%
See 2 more Smart Citations